PENGARUH LINGKUNGAN KERJA DAN ETOS KERJA TERHADAP KINERJA KARYAWAN PADA AL-FITYAN BOARDING SCHOOL BOGOR - Siti Rohmah Indriani; Ryan Bianda; Ahmad Muti (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This research was conducted at Al-Fityan Boarding School Bogor which is located at Jl. Bengkelroda, Kp Cipicung Village, Mekarsari, Kec. Cileungsi, Bogor Regency, West Java. The purpose of this study was to determine the effect of work environment and work ethic on employee performance at Al-Fityan Boarding School Bogor. The research method used is quantitative method. The population in this study were 124 people. The sampling technique used in this study used the slovin formula with a Likert scale measurement scale. The data research used in this study was carried out by distributing questionnaires. Then the resulting data is tested with data quality tests and classical assumption tests, data analysis techniques using validity tests and reliability tests, classical assumption tests, namely normality tests, multicollinearity and heteroscedasticity tests, multiple linear regression hypothesis tests, namely t tests, f tests and R2 determination coefficient tests. Furthermore, this study obtained the results, namely (1) Work Environment (X1) has a positive effect on employee performance (Y), this is indicated by tcount> ttable, namely 2.182> 1.979 and sig value. 0,031 < 0,05. (2) Work Ethic (X2) has a positive effect on employee performance (Y), this is indicated by the tcount> ttable, namely 10,453>1979 and sig value. 0.000 <0.05. (3) Work Environment (X1) and Work Ethic (X2) simultaneously have a positive effect on Employee Performance (Y), this is indicated by Fcount> Ftable, namely 92.883> 3.7 and sig value.0.000 <0.05.